2018
DOI: 10.1158/1535-7163.targ-17-b052
|View full text |Cite
|
Sign up to set email alerts
|

Abstract B052: FLT3-ITD activation mediates resistance to the BCL-2 selective antagonist, venetoclax, in FLT3-ITD mutant AML models

Abstract: 20-25% of acute myeloid leukemia (AML) patients harbor FLT3 internal tandem duplication (ITD) mutations, which confer poorer prognosis. FLT3-ITD is a constitutively activated kinase with differential signaling compared to wild type (WT) FLT3. Notably, FLT3-ITD activates STAT5, which can regulate the prosurvival proteins BCL-XL and MCL-1. Venetoclax, a potent, selective inhibitor of the prosurvival protein BCL-2, demonstrated monotherapy activity in relapsed/refractory AML (ORR 19%); however, no activity was se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 0 publications
0
15
1
Order By: Relevance
“…Furthermore, combination of quizartinib with venetoclax was superior to combination with navitoclax plus AMG 176, suggesting that quizartinib elicits anti-tumor activity outside of its reduction of MCL1 levels. In in vitro studies, they also did not see demonstrable synergy using A1331852 (BCL-X L specific) with quizartinib [14]. Unlike our observations with gilteritinib, no synergism was observed in FLT3-WT using quizartinib, highlighting that there are likely differences in how these two drugs elicit their effects.…”
contrasting
confidence: 81%
See 2 more Smart Citations
“…Furthermore, combination of quizartinib with venetoclax was superior to combination with navitoclax plus AMG 176, suggesting that quizartinib elicits anti-tumor activity outside of its reduction of MCL1 levels. In in vitro studies, they also did not see demonstrable synergy using A1331852 (BCL-X L specific) with quizartinib [14]. Unlike our observations with gilteritinib, no synergism was observed in FLT3-WT using quizartinib, highlighting that there are likely differences in how these two drugs elicit their effects.…”
contrasting
confidence: 81%
“…Therefore, when venetoclax is added to a FLT3 inhibitor, they suggest there is synergy because both MCL1 and BCL2 expressions are reduced, increasing the dampening of the pro-survival activity of the AML blasts. In their work with the combination of quizartinib and venetoclax, Mali et al explored a similar mechanism in vivo in an MV4-11 xenograft model using inhibitors with different selectivities for each of the BCL2 family members in combination: venetoclax (BCL2), navitoclax (BCL2 and BCL-X L ), and AMG 176 (MCL1) [14]. Their results indicated that the improvement in survival was highest when quizartinib was combined with a BCL2, and not MCL1, inhibitor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the findings that clinically used small molecule inhibitors of FLT3 39 , BCR-ABL 17 and Bcl-2 67 increase ceramide levels warrant further investigation. In particular, the combining of two separate drugs such as the FLT3 inhibitor, Quizartinib and the Bcl-2 inhibitor Venetoclax which have demonstrated synergistic cell death in AML, could be partially attributed to the increases in ceramide levels that are produced by each drug 39 , 67 , 97 . Thus this could provide an opportunity for targeted combinational therapies under the premise of synergistic increases in ceramide levels.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing studies were performed to assess the combination of venetoclax and the small molecule FLT3 inhibitor quizartinib in specific FLT3 ITD mutated xenograft models. The combination induced durable tumor regression for up to 3 mo after cessation of treatment[ 83 ]. However, Chyla et al[ 84 ] noted that FLT3-ITD or PTPN11 mutations may confer intrinsic and acquired resistance to venetoclax[ 84 ].…”
Section: Venetoclax + Flt3 Inhibitionmentioning
confidence: 99%